2017
DOI: 10.1016/j.jcis.2017.03.109
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of colloidal structures during intestinal lipolysis using small-angle neutron scattering

Abstract: Hypothesis Bile micelles are thought to mediate intestinal absorption, in part by providing a phase into which compounds can partition. Solubilizing capacity of bile micelles is enhanced during the digestion of fat rich food. We hypothesized that the intestinal digestion of triglycerides causes an increase in volume of micelles that can be quantitatively monitored over the course of digestion using small-angle neutron scattering (SANS), and that SANS can enable evaluation of the contribution of each of the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 60 publications
1
36
1
Order By: Relevance
“…It should be noted that the micelles investigated here could also be cylindrical in shape, making the cylinder model also a plausible fitting model. In a previous study, we have shown that for the micelles investigated here the micellar volume does not change as a function of shape model chosen [152]. The micelle volume is the critical parameter in investigating drug partitioning into the micelle phase, rather than the micelle dimensions.…”
Section: Size Evolution Of Bile Micelles By Triolein Digestion Productsmentioning
confidence: 72%
See 4 more Smart Citations
“…It should be noted that the micelles investigated here could also be cylindrical in shape, making the cylinder model also a plausible fitting model. In a previous study, we have shown that for the micelles investigated here the micellar volume does not change as a function of shape model chosen [152]. The micelle volume is the critical parameter in investigating drug partitioning into the micelle phase, rather than the micelle dimensions.…”
Section: Size Evolution Of Bile Micelles By Triolein Digestion Productsmentioning
confidence: 72%
“…is the total micellar volume per unit solution volume, is the total number of micelles per unit solution volume, 0, is the volume of one micelle in the absence of FA, and are the concentration of MO and OA molecules present in micelles as a function of aqueous bulk volume, respectively, is the Avogadro number, and Ṽ and Ṽ are the volume of one MO and OA molecule, respectively. The average number of micelles per unit solution volume for the specific composition and concentration of bile components and the average volume of one micelle in the absence of MG and FA have been determined previously to be 1.03 x 10 17 micelles/mL and 40 nm 3 [152].…”
Section: Size Evolution Of Bile Micelles By Triolein Digestion Productsmentioning
confidence: 96%
See 3 more Smart Citations